Pokrzywka przewlekła – trudny problem kliniczny. Co jeszcze można zrobić? - Rogala, Barbara (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Numerous factors are proposed to be responsible for chronic urticaria (CU) manifestation. No aetiology is fund in many cases of the diseases in spite of many diagnostic tests available. Chronic urticaria and particularly idiopathic one is extremely disabling and can be difficult to treat. Although it is unusual to identify underlying specific precipitating factors mast cell degranulation is of central importance in the pathogenesis of CU. Update consensus highlights the current achievements in this field concerning both diagnostic procedures and methods of management. The cornestone of CU therapy are antihistaminics which according to the current guidelines could be administered in up to fourfold higher than recommended doses. Immunomodulatory treatments including cyclosporin A, plasmapheresis, intravenous immunoglobulin and-IgE therapy have been also proposed in some group of patients with CU unresponsive to antihistamines.